Efficacy of a telehealth cognitive behavioral therapy for improving sleep and nightmares in children aged 6–17 - Cromer, Lisa DeMarni; Bell, Sarah Beth; Prince, Lauren E.; Hollman, Nicholas; El Sabbagh, Elissar; Buck, Tara R. (Frontiers in Sleep, 2024)
Introduction This study examined the efficacy of a five-module cognitive behavioral therapy for nightmares in children (CBT-NC) and improving sleep. Materials and methods Forty-six youth aged 6–17 years with sleep problems and at least weekly chronic and distressing nightmares were randomized to treatment (n = 23) or waiting list (n = 23) using a block four randomized design. Among participants, 65% (n = 30) were White, 4% (n = 2) were Black/African American, 2% (n = 1) were Asian American, 13% (n = 6) were Native American or Pacific Islander, and 15% (n = 7) were multiracial. Fifty percent of participants (n = 23) were cisgender girls, 35% were cisgender boys (n = 16), 7% were transgender boys (n = 3), and 9% were gender non-binary (n = 4). The baseline nightmare persistence ranged from 6 months to 13.5 years. The treatment adapted exposure, relaxation, and rescription therapy for trauma-related nightmares in adults and added elements of cognitive behavioral therapy for insomnia in children. Psychoeducation included topics of sleep and nightmares, relaxation, anxiety management, and sleep hygiene; the youth were guided through nightmare exposure and rescription. Results There was a statistically significant improvement in the number of nights with awakening (Cohen's d = 1.08), the number of weekly nightmares (Cohen's d = 0.82), and nightmare distress (Cohen's d = 1.05) for the treatment group compared to the wait-list group. Parent-reported youth sleep improved for the entire group from pretreatment to posttreatment (p < 0.001) but did not reach statistical significance for between-subjects analyses of the treatment group compared to the wait-list group (p = 0.05). Between-subjects analyses saw improvement for the treatment group compared to the wait-list group on internalizing and externalizing problems and suicidal thoughts and behaviors. Discussion This study supports the efficacy of CBT-NC for improving sleep maintenance, nightmare frequency and distress, and other mental health difficulties in youth. Preliminary evidence of possibly improving suicidal thinking and behavior is also presented. Clinical trial registration https://clinicaltrials.gov/study/NCT05588739, identifier: NCT05588739.